2021
DOI: 10.1128/aac.00254-20
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tetraphenylborate Displays Selective Bactericidal Activity against Neisseria meningitidis and N. gonorrhoeae and Is Effective at Reducing Bacterial Infection Load

Abstract: Neisseria meningitidis and Neisseria gonorrhoeae, two highly related species that may have emerged from a common commensal ancestor, constitute major human threats. Vaccines are available to prevent N. meningitidis infection, whereas for N. gonorrhoeae, there are only a limited number of antibiotics available. Unfortunately, some strains of these species are rapidly evolving and capable of escaping human interventions. Thus, it is now urgent to develop new avenues to fight these bacteria. This study reports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The human specificity of the pathogen is also a major drawback to studying it. An N. meningitidis B OMV-based vaccine has been evaluated against N. gonorrheae B in clinical trials and found to be only 31% effective ( Bernet et al, 2021 ). Several other vaccines against K. pneumoniae, P. aureginosa, S. enterica, and Shigella sp, are also being developed as already illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The human specificity of the pathogen is also a major drawback to studying it. An N. meningitidis B OMV-based vaccine has been evaluated against N. gonorrheae B in clinical trials and found to be only 31% effective ( Bernet et al, 2021 ). Several other vaccines against K. pneumoniae, P. aureginosa, S. enterica, and Shigella sp, are also being developed as already illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have also been used to test the efficacy of antibacterial compounds. As an example, a model of meningococcal bacteraemia induced following intranasal infection with bacteria was used to demonstrate that administration of sodium tetraphenylborate could significantly reduce bacterial burden [ 223 ].…”
Section: Vertebrate Animal Modelsmentioning
confidence: 99%
“…The markerless strains obtained here emitted a persistent luminescent signal. Of note, luminescent strains of N. meningitidis have been previously used successfully in murine infection models to measure bacterial burden (Alonso et al 2003;Zarantonelli et al 2007;Bernet et al 2020) and the markerless gene modification option is an added advantage.…”
Section: Markerless Gene Insertions In Neisseria Species (Luminescent...mentioning
confidence: 99%